The Urgency of Using Digital-Based Student Learning Activity Instruments to Measure Student Engagement in Distance Learning - Arif Widodo; Angga Prayogi Dwina; Muhammad Syazali; Umar Umar (Institute of Computer Science (IOCS), 2022)
Distance learning in its implementation there still has many obstacles. One of the obstacles in distance learning is that it is difficult for teachers to assess student involvement in learning. Based on these problems, teachers need to be assisted so that an assessment of student involvement in distance learning can be carried out. One of the efforts that can be done is to develop a digital-based learning activity observation instrument. In this study, it will be studied why the use of digital-based instruments is important to development. This research uses a literature study method. The data source comes from the relevant previous research results. Based on the results of the literature study, information was obtained that the use of digital-based instruments has many benefits. The benefits of using digital-based instruments include: it can speed up the assessment process, the implementation of the assessment is more flexible, and transparency of the assessment can be realized. Another benefit of digital-based instruments is that it makes it easier for teachers to collaborate with parents in conducting assessments. With digital-based instruments, it can create a partnership model between teachers and parents in improving the quality of education